Manifestation of Mujahadah on the Cultivation of Emotional Intelligence of Santri Ponpes Nurul Falah Temanggung - Ahmad Sodiqin; Husnul Haq (Amorti: Jurnal Studi Islam Interdisipliner, 2023)
Emotional intelligence is one that has a big influence on success in achieving success in the future is that students are able to be embedded in their souls. Emotional intelligence is one of the major influences on success in achieving success in the future is that students are able to be embedded in their souls . The objectives achieved in this study are: 1) To analyse the form of mujahadah activities that can increase emotional intelligence in students at Pondok Pesantren Nurul Falah Bagusan Selopampang, 2) To analyse the strategy of instilling emotional intelligence in students at Pondok Pesantren Nurul Falah Bagusan Selopampang, 3) To analyse the values of emotional intelligence produced in students at Pondok Pesantren Nurul Falah Bagusan Selopampang. This research uses a qualitative method (field research) with a phenomenological approach. Data collection in this research is done by interview, observation, and documentation. The results of the data that have been collected are analysed using analytical techniques from data reduction, data presentation, and conclusion drawing.This research shows that1) mujahadah activities become a routine agenda at Ponpes Nurul Falah Selopampang which is carried out every day after mahgrib prayer except Friday night, 2) the method of cultivating emotional intelligence that is applied is the Zero Mind Process (ZMP) or the process of cleaning the heart and mind, Mental Building (mental building) which is trying to clear the heart according to its nature, Induvidual Strength (personal resilience), 3) the resulting values are Santri have good spiritual values, Santri can regulate the mood by not being easily provoked or anger. Santri have the value of empathy and prayer, Santri are able to survive with frustration, Santri have a sense of responsibility. The novelty in this research is the cultivation of emotional intelligence in students so that they can use their intelligence appropriately. And that is certainly very different from the planting process in other educational institutions.